URGENT ISSUES OF FURTHER IMPROVEMENT OF PATRIOTIC EDUCATION IN MODERN CONDITIONS - Begimkulov Ilkhom Bairovich (Web of Journals Publishing, 2024)
In this article, honoring the homeland, protecting the homeland, republican-style changes, and the tasks of youth are briefly discussed.
Keywords: Patriotism, Hizb-ut-Tahrir, Jalaluddin Manguberdi.